The Target Language of the Fragment of the "Fuero Real"’s Translation of the Archivo Histórico Provincial de León - Mariño Paz, Ramón (Madrygal. Revista de Estudios Gallegos, 2024)
This paper contains my first contribution to the project of edition and study of the three fragments of translations of the Fuero Real, the Tercera Partida and the Flores de Derecho which are currently deposited in the Archivo Histórico Provincial de León. It is a linguistic analysis that shows that the target language of the first of them is the Galician variety of Vilafranca do Bierzo, with a few adoptions of variants of more eastern varieties. The economic and administrative development that this town reached during the 12th and the 13th centuries turned it into a population with a level of bureaucratic and judicial activity that must have made it necessary to have translations of such legal texts to a variety of romance close to the local one
Keywords: Medieval Galician Prose; Legal Prose; Fuero Real; Translation; History of the Language